Dropouts and Compliance in Exercise Interventions Targeting Bone Mineral Density in Adults: A Meta-Analysis of Randomized Controlled Trials. (3rd June 2013) - Kelley, George A.; Kelley, Kristi S.
Abstract : Background. Dropouts and compliance to exercise interventions targeting bone mineral density (BMD) in adults are not well established. The purpose of this study was to address that gap. Methods. Meta-analysis of randomized controlled exercise intervention trials in adults ≥18 years of age. The primary outcomes were dropouts in the exercise and control groups as well as compliance to the exercise interventions. A random-effects model was used to pool results. Moderator analyses were conducted using mixed-effects ANOVA-like models and metaregression. Statistical significance was set atP ≤ 0.05 . Results . Thirty-six studies representing 3, 297 participants (1, 855 exercise, 1, 442 control) were included. Dropout rates in the exercise and control groups averaged 20.9% (95% CI 16.7%–25.9%) and 15.9% (11.8%–21.1%) while compliance to exercise was 76.3% (71.7%–80.3%). For both exercise and control groups, greater dropout rates were associated with studies conducted in the USA versus other countries, females versus males, premenopausal versus postmenopausal women, younger versus older participants, longer studies (controls only), and high- versus moderate-intensity training (exercisers only). Greater compliance to exercise was associated with being female, home- or facility-based exercise versus both, and shorter studies. Conclusion. These findings provide important information for researchers and practitioners with respect to exercise programs targeting BMD in adults.